2019
DOI: 10.3329/bmrcb.v45i3.44642
|View full text |Cite
|
Sign up to set email alerts
|

Role of XmnI polymorphism in HbF induction in HbE/β and β-thalassaemia patients

Abstract: Background: Thalassaemia is one of the most common genetic blood disorders worldwide. Patients with β-thalassaemia major and HbE/β-thalassaemia are blood transfusion dependent. Foetal haemoglobin or HbF can play a role in disease manifestations in these patients and there is evidence that a homozygous state for XmnI polymorphic site, associated with increased expression of Gγ-gene, may play an important role among other factors in ameliorating the clinical severity of homozygous β-thalassaemia and thalassaemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…The XmnI polymorphism is a common genetic variation that was reported in previous studies to increase HbF level and therefore ameliorate the severity of the sickle cell disease.Our study shows that a polymorphism of the XmnI was found to be associated with higher expression of HbF in sickle cell and sickle cell trait patients. Several studies confirmed the association between XmnI and fetal hemoglobin 10,11 .Appositive association was observed between the HbF level and the presence of Xmn1 site in SS and sickle thalassemia groups Recently, other genetic association studies shown that several single nucleotide polymorphisms, associated with variation in the expression of HbF in sickle cell disease 12 .The XmnI polymorphism is known to influence the γ G gene expression in sickle cell anemia and to increased HbF concentrations when they are under conditions of erythropoietic stress 13 . Study conducted by FarizKahhaleh et.al to assist the Association of Xmn1 polymorphism and consanguineous marriage with fetal hemoglobin in Syrian patients with sickle cell disease they concluded that a strong evidence on the importance of Xmn1 polymorphism and consanguineous marriage, among other factors, in the prediction of clinical severity and hydroxyurea response in SCD patients 14 .…”
Section: Discussionmentioning
confidence: 85%

Association of XmnI Polymorphism with Fetal Hemoglobin Level in Sudanese Patients with Sickle Cell Disease

Tarig Osman Khalafallah Ahmed,
Abeer Alshazaly Abdulrahman Altag,
Ahmed Abdalla Agab Eldour
et al. 2021
IJOCM
“…The XmnI polymorphism is a common genetic variation that was reported in previous studies to increase HbF level and therefore ameliorate the severity of the sickle cell disease.Our study shows that a polymorphism of the XmnI was found to be associated with higher expression of HbF in sickle cell and sickle cell trait patients. Several studies confirmed the association between XmnI and fetal hemoglobin 10,11 .Appositive association was observed between the HbF level and the presence of Xmn1 site in SS and sickle thalassemia groups Recently, other genetic association studies shown that several single nucleotide polymorphisms, associated with variation in the expression of HbF in sickle cell disease 12 .The XmnI polymorphism is known to influence the γ G gene expression in sickle cell anemia and to increased HbF concentrations when they are under conditions of erythropoietic stress 13 . Study conducted by FarizKahhaleh et.al to assist the Association of Xmn1 polymorphism and consanguineous marriage with fetal hemoglobin in Syrian patients with sickle cell disease they concluded that a strong evidence on the importance of Xmn1 polymorphism and consanguineous marriage, among other factors, in the prediction of clinical severity and hydroxyurea response in SCD patients 14 .…”
Section: Discussionmentioning
confidence: 85%

Association of XmnI Polymorphism with Fetal Hemoglobin Level in Sudanese Patients with Sickle Cell Disease

Tarig Osman Khalafallah Ahmed,
Abeer Alshazaly Abdulrahman Altag,
Ahmed Abdalla Agab Eldour
et al. 2021
IJOCM